profile
Опубликовано 10 месяцев назад по предмету Алгебра от масяня3009

1.  sin(x + frac{2pi}{3} ) * sin(x - frac{pi}{3}) <br />
2.  sin(x + frac{pi}{4} ) * sin(x - frac{pi}{3})

  1. Ответ
    Ответ дан Artem112
     sin(x + frac{2pi}{3} )  sin(x - frac{pi}{3}) = \ =0,5(cos(x + frac{2pi}{3}-x+ frac{pi}{3})-cos(x + frac{2pi}{3}+x - frac{pi}{3}))=
\ =0,5(cospi-cos(2x + frac{pi}{3} ))=-0.5-0.5cos(2x + frac{pi}{3} )

     sin(x + frac{pi}{4} )  sin(x - frac{pi}{3}) = \ =0,5(cos(x + frac{pi}{4}-x+ frac{pi}{3})-cos(x + frac{pi}{4}+x - frac{pi}{3}))=
\ =0,5(cos frac{7pi}{12}-cos(2x- frac{pi}{12}))=
0,5cos frac{7pi}{12}-0.5cos(2x- frac{pi}{12})
Самые новые вопросы